When aid misses the target: competing objectives, new classifications, and smarter delivery - Dreher, Axel (World development, 2025)
Western donors allocate over US$ 200 billion annually to official development assistance (ODA), yet much of this funding serves goals other than sustained recipient‑country development. In this paper, I argue that competing objectives and uses—including in‑donor refugee costs, geopolitical interests, and commercial ties—and inflated aid budgets undermine ODA’s credibility. I then argue for a narrow, development‑focused definition of ODA that excludes humanitarian relief and global public goods and suggest that concentrating development aid on infrastructure, education, and health—linked to a small number of ex ante conditions and delivering it primarily through budget support in democracies—would improve alignment with recipient priorities, bolster government accountability, and maximize developmental impact.